PENGARUH MOTIVASI BERWIRAUSAHA DAN LINGKUNGAN SOSIAL TERHADAP MINAT BERWIRAUSAHA (Studi Kasus pada Dusun Beton Desa Tritunggal Kecamatan Babat Kabupaten Lamongan) - Alifia, Isye Fera; Dwiridho, jojok (Jurnal Bisnis Indonesia, 2019)
This study aims to determine the influence of: (1) Entrepreneurship Motivation and Social Environment on Entrepreneurship Interest in Beton Hamlet people. (2) Entrepreneurship Motivation on Entrepreneurship Interest in Beton Hamlet people. (3) Social Environment on Entrepreneurship Interest in Beton Hamlet people.  This study is quantitative research. The population of this study  is 163 Beton Hamlet people as convection business owner. The sample is 116 respondents among them. The probability sampling technique was employed to obtain the sample of the study. The data of this study were obtained through questionnaires. Analysis Prerequisite Test of this study consisted of multicolinearity test, autocorrelation test, heteroscedasticity test, and normality test. Multiple linear regression technique were employed as the data analysis technique. The result shows that: (1) Simultaneously, there is a positive and significant influence of Entrepreneurship Motivation and Social Environment on Entrepreneurship Interest in Beton Hamlet people (2) Partially, there is a positive and significant influence of Entrepreneurship Motivation on Entrepreneurship Interest in Beton Hamlet people. (3) Partially, there is a negative and significant influence of Social Environment on Entrepreneurship Interest in Beton Hamlet people. This is becauseBeton Hamlet people can not immediatelly accept the influence of Social Environment (external factor) in fostering Entrepreneurship Interest. Other factors are needed that can support the Entrepreneurship Interest, especially from internal factors. Entrepreneurship Interest is the most dominant variable influencing on Entrepreneurship Interest in Beton Hamlet people Tritunggal Village Babat District Lamongan Regency. Keywords: Entrepreneurship Motivation, Social Environment, Entrepreneurship Interest.